Pengembangan E-Modul Kontekstual Interaktif Berbasis Web pada Mata Pelajaran Kimia Senyawa Hidrokarbon - Nalarita, Yulia; Listiawan, Tomi (MULTITEK INDONESIA, 2018)
Supporting the implementation of effective learning process, can not be separated from the use of teaching materials that is module. Modules are also developed in electronic form / format called emodules E-module Is an interactive module that displays / loads images, audio, video and animations that are packaged in a Web base of hydrocarbon compound subjects. Educators are expected to teach  the  learning in the real world so that students are able to remember, understand, and apply the science in everyday life called contextual learning. Techniques of data collection using interviews, questionnaires and observations used to obtain data aspects of functionality and usability. The instrument used in the aspect of functionality using four Likert scales is very feasible, feasible, less feasible, and not feasible. For usability instrument use four likert scale that strongly agree, agree, disagree, and disagree. In portability aspect use 4 web browser that is Mozilla Firefox, Google Chrome, Internet Explorer, and Opera as testing. On the efficiency aspect of using GTMetri application that produces 2 tests, namely YSlow put forward by Yahoo Developer Network and PageSpeed Insights recommended by Google Developer. From the result of data analysis, the functionality aspect of the media expert produces the value of functionality (X) of 1. For the data of the functionality aspect of the material expert gives a value of 90.79% which indicates a very feasible value. From the test results portability aspect using 4 types of web browsers to produce data in the form of all web browsers succeed, but there is a problem in the resolution that resulted in the display becomes small. From the results of the efficiency resulted in an average score of pagespeed of 97.5% and for the yslow score yielded an average score of 96.5%. For usability aspect yield score 80,02% with criterion score that is agree